2003
DOI: 10.1210/jc.2002-030026
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Determination of Bone Mineral Density: Evidence for a Major Gene

Abstract: This study was designed to test the hypothesis of a major gene influence on the variation in bone mineral density (BMD). BMD and bone mineral content at the lumbar spine and femoral neck were measured in 330 men and 413 women, aged 18-90 yr, from 107 nuclear and complex families (including 5 large pedigrees with 194 individuals who were identified through an index case with moderately high BMD at the femoral neck (z-score, >or=1.28)). After adjusting for age and body weight, familial factors accounted for up t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 33 publications
1
29
0
Order By: Relevance
“…This study used data from three independent populations in Australia, the United States, and Chuvasha (Russian Autonomous Republic). Details of the study design of the studies have been described previously (6–8) . Characteristics of the study subjects are shown in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…This study used data from three independent populations in Australia, the United States, and Chuvasha (Russian Autonomous Republic). Details of the study design of the studies have been described previously (6–8) . Characteristics of the study subjects are shown in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…In osteoporosis, perturbations in local cytokines, growth factors, systemic hormones and transcription factors cause imbalance between bone formation and resorption, resulting in net bone loss (Karsenty, 1999). Peak bone mass, the result of net bone accrual in early life and with a maximum in the second and third decade of life, is greatly influenced by genetic factors (50-85%) (Giguere and Rousseau, 2000;Ralston, 2002;Nguyen et al, 2003;Ralston and de Crombrugghe, 2006). BMD depends on peak bone mass, but also on the rate of bone loss in later life.…”
Section: Introductionmentioning
confidence: 99%
“…(3)(4)(5)(6)(7) Architectural properties of whole bone, as well as trabecular bone, typically display continuous distributions within the population and are considered to be complex, quantitative traits. Complex traits can be influenced by many different genes functioning in concert.…”
mentioning
confidence: 99%